Congenital orbital teratoma: A case report - Ahmed Raza; Asma Mushtaq; Seema Qayyum; Fiza Azhar; Ahmad Imran; Ashvinah Qayyum (EL-Med-Pub, 2020)
Background: Teratoma originates from all three germinal layers and commonly found at the sacrococcygeal region. The orbit is an unusual site of occurrence, but they grow rapidly and cause massive proptosis. Case Presentation: A 9-day-old female neonate presented with marked unilateral proptosis of the right eye. Imaging workup gave a suspicion of a complex mass with internal hemorrhage or a teratoma. Modified exenteration was performed. Histopathological examination revealed mature cystic teratoma. Conclusion: Orbital teratoma presents with marked disfiguring proptosis in neonatal life. Prompt complete surgical excision is curative in the case of mature lesions.